Peningkatan Produksi Minyak Kelapa dengan Cara Fermentasi di Kabupaten Bulukumba - Suriati Eka Putri; Ramdani Ramdani; Pince Salempa (DEDIKASI, 2019)
The purpose of this activity was to convey the use of science and technology in increasing coconut oilproduction in the village of Tugondeng, Herlang District, Bulukumba Regency. Based on the identification of theproblem, the process of making coconut oil in the village of Tugondeng is still traditional, without the developmentof science and technology. Thus, the community service program team provided counseling on the process ofmaking coconut oil by fermentation. The results obtained show that the process of making coconut oil byfermentation only takes a short time in the heating process in order to minimize energy usage.